2022
DOI: 10.1038/s41421-022-00415-0
|View full text |Cite
|
Sign up to set email alerts
|

Single-cell multiomics analysis reveals regulatory programs in clear cell renal cell carcinoma

Abstract: The clear cell renal cell carcinoma (ccRCC) microenvironment consists of many different cell types and structural components that play critical roles in cancer progression and drug resistance, but the cellular architecture and underlying gene regulatory features of ccRCC have not been fully characterized. Here, we applied single-cell RNA sequencing (scRNA-seq) and single-cell assay for transposase-accessible chromatin sequencing (scATAC-seq) to generate transcriptional and epigenomic landscapes of ccRCC. We id… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
34
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(38 citation statements)
references
References 106 publications
4
34
0
Order By: Relevance
“…Previous studies have established CA9 as a marker for ccRCC tumor cells [15,[31][32][33]. Consistently, our ndings showed that CA9 + nephrons originated from tumor tissue and exhibited a distinct distribution compared to adjacent normal tissue (Fig.…”
Section: The Differential Tumor Microenviroment Of Primary Lesion Bet...supporting
confidence: 89%
“…Previous studies have established CA9 as a marker for ccRCC tumor cells [15,[31][32][33]. Consistently, our ndings showed that CA9 + nephrons originated from tumor tissue and exhibited a distinct distribution compared to adjacent normal tissue (Fig.…”
Section: The Differential Tumor Microenviroment Of Primary Lesion Bet...supporting
confidence: 89%
“…Moreover, single-cell multi-omics approaches enable simultaneously profiling a couple of omics in identical cells [288], providing information on both regulatory elements and consequential gene expression levels for individual cells. The datasets generated by these technologies may help biomedical researchers to discover disease-specific regulatory programs, possibly in the subset of certain cell types [289]. Furthermore, although still in the developmental stage, spatial transcriptomics is a promising technique for considering the cellular context in molecular features of a particular cell [290].…”
Section: Discussionmentioning
confidence: 99%
“…Single-cell mRNA sequence (scRNA-seq) data from 4 ccRCC patients with 4 tumor samples (1 sample is assigned to 1 patient), 1 VHL-mutated sample and 3 VHL-wild samples, were collected from Young, et al cohort [ 13 ] and another dataset from Long cohort [ 14 ] including 4 samples from 4 ccRCC patients, all the patients were VHL mutated in Long cohort. After preliminary sample integration and quality control of scRNA-seq data sets, we generated a gene expression matrix with 76,118 cells.…”
Section: Methodsmentioning
confidence: 99%